Functional group analysis of cigarette butts in beach sand and their association with microplastics: Bocagrande Beach, Cartagena, Colombia - Claudia Díaz-Mendoza; Javier Mouthon-Bello; Camilo M. Botero; Juan Valdelamar Villegas; Leonardo Gutiérrez; Keydis Martinez-Villadiego (PLoS ONE, 2026)
Cigarette butts are one of the most abundant litter items on beaches and represent an emerging source of microplastic pollution due to the degradation of their cellulose acetate filters. When improperly discarded on beach sand, cigarette butts release chemical contaminants and undergo physical and photo-oxidative fragmentation, generating persistent fiber-type microplastics in coastal environments. This study assessed the presence and characteristics of microplastics (MPs) associated with cigarette butt (CB) and cigarette butt fiber (CBF) residues in beach sand at a pilot tourist site. Monthly sampling was conducted across 16 campaigns between 2021 and 2022 to evaluate temporal trends in microplastic categories. Triplicate samples of CBs, CBFs, and beach sand were collected from usage-based zones and analyzed using Fourier-transform infrared spectroscopy (FTIR) to identify functional groups and polymeric composition. The results indicated that 44% of the CB-related functional groups reported in the literature were detected in the service area, with 36% associated with cellulose acetate degradation. The correspondence between functional groups identified in CBs and those detected in fiber-type MPs in sediments suggests that cigarette butts constitute a relevant source of hazardous MP fibers in beach environments. These findings support the need for improved waste management strategies and policy measures aimed at reducing CB pollution in coastal areas.